Media Sosial dan Gaya Hidup Wanita Di Indonesia - utomo, bambang setyo; Pawito, Pawito (UIN Sunan Kudus, 2017)
The development of communications technology today is increasingly fast and gives a variety of effects and impact on human life. Since internet technology has been activated and the emergence of Web 2.0 innovations in the early 2000s has attracted social media has become a major concern in recent years. Indonesian women who are the most current users of social media in using social media are not just for reasons to make friends but on the other hand they use social media in financial terms. There is a trend that is currently using social media to open a business. In addition to these trends, women with their ability to build networks and communicate have presented some phenomena in their lifestyle